(untitled) (Swiss Medical Weekly, 2013)
DNA methylation, the addition of a methyl group to cytosines and adenosines, regulates gene expression on a level that is usually referred to as epigenetic, that is, stably maintained during cell divisions. In humans, aberrant DNA methylation is associated with several malignancies, including cancer and so-called imprinting disorders, making it an attractive target for diagnostic purposes. Here we give a brief introduction to the biology of DNA methylation and present the use of methylation biomarkers in laboratory medicine. DNA methylation assays have become the standard procedure in the diagnosis of imprinting disorders, and they are about to shift cancer diagnostics and prognostics to the next level of molecular medicine. However, there is evidence of problems associated with the introduction of such cancer assays in routine diagnostics. We review several assays that have been proposed for DNA methylation analysis. The assays presented analyse the methylation status of single loci and are based either on a bisulphite-treatment or on methylation-sensitive restriction of the DNA under investigation.